2021
DOI: 10.1186/s12903-021-01859-8
|View full text |Cite
|
Sign up to set email alerts
|

The cross-sectional effects of ribbon arch wires on Class II malocclusion intermaxillary traction: a three-dimensional finite element analysis

Abstract: Background The application of intermaxillary traction is often accompanied by the unexpected movement of dentition, especially anchorage teeth. The aim of this study was to comprehensively compare the influence of cross-sectional shape of ribbon arch wires with edgewise and round wires on intermaxillary traction in Class II malocclusion treatment using FEA simulation. Methods The dentofacial structure was simulated in finite element software. A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The Forsus FRD showed intrusion of the upper molars and lower incisors. Our results agree with diverse clinical studies of the studied appliances (Aras and Pasaoglu, 2017; Cacciatore et al, 2014a; Jones et al, 2008; Kim-Berman et al, 2019; Xie and Li, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The Forsus FRD showed intrusion of the upper molars and lower incisors. Our results agree with diverse clinical studies of the studied appliances (Aras and Pasaoglu, 2017; Cacciatore et al, 2014a; Jones et al, 2008; Kim-Berman et al, 2019; Xie and Li, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we also found the highest concentration of stress in the lower arch at the first molars in the Class II elastics model, but we noted compressive stress in the buccal distal region and tensile stress in the mesial cervical region. Xie and Li (2021) found that with Class II elastics, the highest von Mises yield in the lower arch at the PDL was located in the distal root of the first molars, which decreased gradually in the mesial direction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ethnic differences may, however, play a role: prevalence of PO in CKD patients was more important in non-Hispanic Blacks and Mexican Americans, but not so in non-Hispanic Whites in the National Health and Nutrition Examination Survey (NHANES) cohort [24]. As CKD progresses, the prevalence of PO increases, being more important in advanced stages [4,6] when compared to earlier stages of CKD [25,26]. In dialysis patients, the prevalence of PO exceeds 50% of patients [27][28][29][30], and in some reports approaches 100% in peritoneal [31] and hemo-dialysis (HD) patients [32].…”
Section: Association Of Po and Ckdmentioning
confidence: 99%
“…However, increased cardiovascular risk and mortality is also present in pre-dialysis stages, with CKD being a major cardiovascular risk factor [4]. Mortality, morbidity, and impaired quality of life in CKD patients result in significant decrease in disease-adjusted life years associated with this condition [6]. There are efficient ways to decrease progression of CKD and improve outcomes of these patients.…”
Section: Introductionmentioning
confidence: 99%